Knowledge management and information and communication technologies (ICTs) in mechanical engineering students - Ocaña Fernández, Yolvi (2020)
The purpose of this research was to determine the relationship between knowledge management and information and communication technologies (ICTs), based on the quantitative approach and the deductive hypothetical method, with a basic type of research. The executed research design was non-experimental. The survey technique was used and two instruments applied to knowledge management and ICTs were developed as instruments, with the reliability values ​​of 0.929 and 0.869 respectively. The results of the investigation determined that there is a direct relationship between knowledge management and ICTs with a value of 830 for the Spearman correlation coefficient, confirming that there is a significant relationship between both variables in a sample of 154 students. It was concluded that there is a relationship between knowledge management and information and communication technologies among students of the specialty of mechanical engineering at a particular university in Lima.